Nanofluid Transport through a Complex Wavy Geometry with Magnetic and Permeability Effects - Muhammad Saleem Iqbal; Abuzar Ghaffari; Arshad Riaz; Irfan Mustafa; Muhammad Raza (Inventions, 2021)
The current article incorporates the numerical investigation of heat exchange rate and skin friction carried out through nanofluid saturated with thermally balanced porous medium over a rough horizontal surface that follows the sinusoidal waves. The effects of the external magnetic field are discussed by managing the magnetic field strength applied normally to the flow pattern. The occurring partial differential governing equations are grasped through a strong numerical scheme of the Keller box method (KBM) against the various parameters. The findings are elaborated through tables and diagrams of velocity, temperature, skin friction, Nusselt number, streamlines, and heat lines. The percentage increase in Nusselt number and coefficient of skin friction over the flat and wavy surface is calculated which leads to the conclusion that the copper (Cu) nanoparticles are better selected as compared to the silver (Ag) for heat transfer enhancement. It is also evident from sketches that the current analysis can be used to enhance the surface drag force by means of nanoparticles. It is a matter of interest that the magnetic field can be used to manage the heat transfer rate in such a complicated surface flow. The current readings have been found accurate and valid when compared with the existing literature.